TANGGUNG JAWAB MANTAN KARYAWAN NOTARIS SEBAGAI SAKSI AKTA TERHADAP KERAHASIAN AKTA - Hatta Isnaini Wahyu Utomo; Imam Safi'i (Res Judicata, 2019)
Witness Notary deed are the witnesses who participated in the making of the deed (instrument), Task instrumentarir witness is his signature, bear witness of the truth of the deed and the fulfillment of the formalities required by the Act. In the manufacture of authentic deed Notary often use employees to witness the deed given witness notary deed should have been known, especially to do with confidence. Generally occurs when there are people who have become former employees, or did not work in places where he used to work would have thought that any liability related to previous work has been completed because there is no relationship of interdependence in such work. This resulted confidentiality deed known by former employees who witnessed the deed leaked to unauthorized parties. Until now Notary Public Functional Position (Undang-Undang Jabatan Notaris) has not been set on the responsibility of the witness and former employee of the notary deed as witnesses deed